2002
DOI: 10.1021/ef0102925
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chlorine−Alkali−Mineral Interactions during Co-Combustion of Coal and Straw

Abstract: During co-combustion of coal and straw, ash deposition and pollutants (HCl, aerosols, etc.) formation is significantly influenced by the behavior of chlorine and alkali metals. On the bases of measurement data, the effect of inherent minerals in blended fuels on the release and retention of chlorine and alkali metals is investigated through the equilibrium analysis tool FACT-Win. Si, Al, Ca, Mg, and S may greatly affect the behavior of Cl, K, and Na, where the other minor elements, such as Fe, Ti, and Mn have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Most of the studies involving co-firing coal and straw have focused on the speciation of alkali metals and the reactions of alkali metal with chlorine to determine the properties of fly ash deposits [284][285][286][287]; although equilibrium models have some limitation (no consideration is given to kinetics, gas phase is assumed ideal, perfect mixing prevail that all elements are available for reaction). Significant amounts of K are released in the gas phase as KCl and KOH [284] as well as K 2 SO 4 [284,[288][289][290] have studied reactions involving the reactions of these species with other species present in the gas phase. Zheng et al [273] observed that the K content in the fly ash is almost the same as that in the fuel ash during combustion and co-combustion involving straw.…”
Section: Prediction Of Coal-biomass Ash Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies involving co-firing coal and straw have focused on the speciation of alkali metals and the reactions of alkali metal with chlorine to determine the properties of fly ash deposits [284][285][286][287]; although equilibrium models have some limitation (no consideration is given to kinetics, gas phase is assumed ideal, perfect mixing prevail that all elements are available for reaction). Significant amounts of K are released in the gas phase as KCl and KOH [284] as well as K 2 SO 4 [284,[288][289][290] have studied reactions involving the reactions of these species with other species present in the gas phase. Zheng et al [273] observed that the K content in the fly ash is almost the same as that in the fuel ash during combustion and co-combustion involving straw.…”
Section: Prediction Of Coal-biomass Ash Behaviormentioning
confidence: 99%
“…They concluded that the total K in the fly ash can be predicted when the ash composition of the fuel and straw share are known. Na is likely to be released as NaCl, NaOH, NaSO 4 and Na [284] and react with the gas phase compounds. These observations corroborate with the fuel characterization based on the reactive and non-reactive ash-forming matter.…”
Section: Prediction Of Coal-biomass Ash Behaviormentioning
confidence: 99%
“…At this point the fouling index F i [29,30] is introduced for a first assessment of the fouling behavior of the two coals. The fouling in dex is given in Eq.…”
Section: Fuels Composition and Deposition Predictionmentioning
confidence: 99%
“…have significant influence on the behaviour of chlorine and alkali metals [24][25][26][27][28][29][30][31]. In fact, it may be affected by many factors, such as composition of the fuel, combustion or gasification conditions, and low or high pressure.…”
Section: Introductionmentioning
confidence: 99%